Analysis of 11th grade Senior High School Students Scientific Literacy on Salt Hydrolysis Lesson - Masrid Pikoli; Wahyuningrum Istiqomah; La Alio (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to determine the scientific literacy ability of class XI science students of SMAN 1 Suwawa and SMAN 1 Kabila on salt hydrolysis material, with a sample of 243 students. This type of research is descriptive qualitative. This study measured scientific literacy skills using the Test of Scientific Literacy Skills (TOSLS) instrument. The literacy questions used in this study amounted to 20 multiple-choice questions that had been tested for validity with a high level of validity (87%). The results showed that the data obtained on the results of scientific literacy skills of class XI science students consisted of SMAN 1 Suwawa with a percentage of 33.53% and SMAN 1 Kabila with 30.44% overall in the low category.